1996
DOI: 10.1016/0885-3924(95)00148-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphine and morphine-6-glucuronide plasma concentrations and effect in cancer pain

Abstract: The relationships between plasma morphine and metabolite (M3G and M6G) concentrations and analgesic efficacy were investigated in an open study of 39 cancer pain patients receiving chronic oral morphine therapy with either morphine sulfate solution or controlled-release morphine tablets. There were no differences in morphine, metabolite kinetics, or analgesic efficacy between equivalent doses of conventional or controlled-release formulations. The increase in morphine plasma concentration after a dose (1 hr fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 19 publications
3
45
1
Order By: Relevance
“…This is at odds with the hypothesis of "toxic" concentrations of either the opioid or its metabolites as major contributors to the pathogenesis of AE [5]. Conversely, individual patterns in opioid metabolism and in the distribution of opioid receptors and their functional networks should be discussed as relevant (perhaps genetically fixed) factors influencing individual responsiveness to or tolerability of opioids as suggested by the number of patients requiring multiple changes [6,15,27]. In the present study, 6 out of 8 patients changing opioids because of AE received morphine in spite of impaired renal function.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This is at odds with the hypothesis of "toxic" concentrations of either the opioid or its metabolites as major contributors to the pathogenesis of AE [5]. Conversely, individual patterns in opioid metabolism and in the distribution of opioid receptors and their functional networks should be discussed as relevant (perhaps genetically fixed) factors influencing individual responsiveness to or tolerability of opioids as suggested by the number of patients requiring multiple changes [6,15,27]. In the present study, 6 out of 8 patients changing opioids because of AE received morphine in spite of impaired renal function.…”
Section: Discussionmentioning
confidence: 93%
“…The involvement of active metabolites in the development of opioid side effects has been shown for morphine-3-glucuronide and morphine-6-glucuronide, which accumulate in patients with renal injury [2, 15,34,35]. The impact of an individualized pharmacodynamic is obvious for methadone and for oral morphine [11,37,38].…”
Section: Introductionmentioning
confidence: 98%
“…One study suggested, for example, that up to 89% of plasma methadone is protein bound (Inturrisi et al, 1987), thereby possibly reducing the in vivo amount of methadone available to inhibit I HERG to 11% (free fraction) and raising the therapeutic index for methadone approximately 10-fold. Drug metabolites may also play a role, because the metabolites for some opioid compounds can attain plasma concentrations that are Ͼ60-fold higher than those achieved by the parent drug (Faura et al, 1996). In addition, one has to consider drug formulations.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of morphine clearance would result in increased plasma morphine concentrations, which would be expected to increase analgesia. However, M6G is a more potent µ opioid agonist [1] and a number of studies have shown its contribution to analgesia, particularly after a high dose or during chronic morphine therapy [2,3,51,52]. In contrast, several animal studies have shown that M3G attenuates the opioid effects of morphine [5,6,53,54], although this has yet to be well demonstrated in humans.…”
Section: Tablementioning
confidence: 99%